SEKOLAH RAKYAT PROGRAM AFIRMASI SEKOLAH BERMUTU DAN PENGENTASAN KEMISKINAN - Tumpal Daniel S; Juhaeriah Juhaeriah (STAI Darul Qalam Tangerang, 2025)
The People's School, a free, affirmative action program for quality schools for the poor, is an investment in the future. Targeting students from poor families in deciles 1 and 2, with monthly incomes of between eight hundred thousand and two million rupiah, the People's School provides formal elementary, middle, and high school education. The goal is for graduates to achieve and be job-ready, becoming gamechangers, breaking the cycle of poverty in their families. This article uses a qualitative research approach to generate descriptive data on the effectiveness of the affirmative action program that provides poor families with access to quality schools. The conclusion is that the People's School meets the standards of a free, quality school and requires regulations higher than the Presidential Instruction (Inpres) as the legal basis for its implementation.